2021
DOI: 10.12688/wellcomeopenres.16767.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Timing of whooping cough Immunisation in MUMs: a randomised controlled trial investigating the timing of pertussis vaccination in pregnancy (OpTIMUM): a protocol paper

Abstract: Background: Pertussis is a highly infectious respiratory illness caused by the bacteria Bordetella pertussis. A resurgence of pertussis, even in countries with good vaccine coverage, has led to an increase in infant deaths. In response to this, many countries have introduced pertussis vaccination in pregnancy. This strategy is effective at preventing infant disease, but there remains uncertainty about what gestational timing is best to ensure maximal protection of the infant. These uncertainties are the ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…37 A recent study showed that vaccine administered between 16 and 32 weeks of pregnancy provided similar levels of antipertussis toxin and antipertactin IgG concentrations. 38 However, antifilamentous hemagglutinin IgG concentrations were shown to be increased with advanced gestational age at the time of vaccination in pregnancy that is between 28 and 32 gestational weeks. 38 Another factor in optimizing vaccine effectiveness is prematurity.…”
Section: Timing Of Vaccinati Onmentioning
confidence: 99%
See 2 more Smart Citations
“…37 A recent study showed that vaccine administered between 16 and 32 weeks of pregnancy provided similar levels of antipertussis toxin and antipertactin IgG concentrations. 38 However, antifilamentous hemagglutinin IgG concentrations were shown to be increased with advanced gestational age at the time of vaccination in pregnancy that is between 28 and 32 gestational weeks. 38 Another factor in optimizing vaccine effectiveness is prematurity.…”
Section: Timing Of Vaccinati Onmentioning
confidence: 99%
“…38 However, antifilamentous hemagglutinin IgG concentrations were shown to be increased with advanced gestational age at the time of vaccination in pregnancy that is between 28 and 32 gestational weeks. 38 Another factor in optimizing vaccine effectiveness is prematurity. An independent risk factor for severe morbidity and mortality related to pertussis infection is indeed preterm birth.…”
Section: Timing Of Vaccinati Onmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported equivalent concentrations of IgG antibodies in infants born to mothers who received the pertussis vaccine at 3 different time intervals in pregnancy, supporting a broader interval of 16–32 weeks. 1 Safety evaluations of the Tdap vaccine have not revealed any significant concerns associated with its use during pregnancy. Maternal vaccination with a pertussis-containing vaccine leads to elevated antibody levels in newborns, which persist for at least 2–3 months.…”
Section: Current Vaccinesmentioning
confidence: 99%
“…11 Finally, an observational study from Switzerland in 2016 showed that anti-pertussis toxin and anti-filamentous haemagglutinin concentrations were higher in cord blood following vaccination in the second trimester than following vaccination in the third trimester. 12 Following this report, and mindful of the logistical benefits of offering vaccination in a wider time window, the UK extended the recommended window for vaccination to [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] weeks in 2016.…”
Section: Introductionmentioning
confidence: 99%